(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
This paper looks at a number of existing theories of human development from an existential-phenomenological perspective. Most existing theories are stage theories which attempt to find common factors in human development in terms of invariant stages, phases or periods. Human development therefore is in terms of movement from one stage to the next. It is suggested that this passive view of human life is incompatible with an existential-phenomenological perspective because it does not take into account the givens of existence i.e. the primacy of time, death, freedom and responsibility to make meaning, and the lived body. An alternative existential model is proposed whereby the person moves towards a greater understanding and ownership of their existence in a world of others through encounters with largely chance events which they make, to a greater or lesser extent, a part of their own autobiography.